Finance and Development, September 1985. (Finance and Development; Finance and Development ;, 1985)
This paper highlights that international flows of capital can promote global economic efficiency and can allow countries with balance-of-payments deficits to strike the right balance between reducing their deficits and financing them. The IMF's evolution into an effective international organization is largely attributable to its ability to adapt its activities, policies, policymaking bodies, procedures, and even its Articles in response to changing circumstances. The growth of developed and developing countries is closely linked, but better policy coordination and financial intermediation are needed.